Producto radial :discriminación en pacientes con V.I.H - Pérez Vargas, Fanny Janet (2017)
This research is established as an academic project through which is addressed theoretically the educational role of radio in the demystification of people living with HIV, for which it uses the position of different authors who have addressed the origin of this media, its features and functions, and the mechanisms by which it can influence the opinions of people about the myths generated about communicable diseases and catastrophic illnesses. Furthermore, as the end result of this project a total of 15 radio spots is presented, through which it seeks to reduce the level of discrimination against people with HIV, because as evidenced by the survey that those patients attending applied the HIV clinic of Enrique Garcés Hospital, many of the myths built around this infection are generated because of misinformation and fear of infection, situations that have been addressed in these radial parts of a creative dynamic, and from the same voice of those affected, in order to generate a change as to the way of thinking in the Ecuadorian population, the impact of psychosocial problems and public health.